Comportamento de diferentes genótipos de Eucalyptus spp. expostos a um baixo suprimento do fósforo em solução nutritiva - Aguilar, Marcos Vinícius Miranda (2021)
The nutritional efficiency of phosphorus (P) in plants is desirable, since it is related to the increase in biomass production, increase in shoot and roots, and consequently can influence productivity, fertilizer savings, and reduction in nutrient exports. Thus, the present study aimed to verify the behavior of different genotypes of Eucalyptus spp. exposed to a low supply of phosphorus in nutrient solution to select more efficient phosphorus genotypes. A completely randomized experimental design was adopted, with three replications, in a 3 x 4 factorial scheme, with the effect of three phosphorus doses (100% P (standard level of P), 30% P (low level of P) and 10 % P (very low level of P) of the standard concentration of P in the Hoagland nutrient solution, and four genotypes of Eucalyptus spp. (Eucalyptus saligna, Eucalyptus urograndis, Eucalyptus dunnii and Eucalyptus globulus). Each sample unit consisted of a pot containing three plants, totaling 36 experimental units. After 18 days of exposure to different treatments in a hydroponic system, the morphological parameters of the shoot and root system were evaluated, photosynthetic variables, chlorophyll a fluorescence, photosynthetic pigments, activity of antioxidant enzymes and acid phosphatase. E. saligna showed no significant difference between the level of 30% P and control treatment (100% P) for the variables MSPA, MSR and MST, while E. urograndis showed the highest rate of liquid assimilation and the lowest rate of transpiration at the level of 30% P. For the initial fluorescence, it was observed that only E. dunnii showed a difference between the levels of P tested. E. saligna, E. urograndis and E. globulus showed no significant difference between the different levels of P for the activity of the enzyme guaiacol peroxidase in the roots. The positive response observed in the morphophysiological and biochemical attributes of the seedlings of E. urograndis by reducing the fertilization of P (30% P) reflect the low requirement of the species in relation to soil fertility, without restricting the production of biomass, and the extension of the root area under low nutrition of P. However, there was no growth of E. globulus seedlings at any of the tested P levels. The 10% P level did not allow the production of seedlings with desirable morphological characteristics for any of the genotypes in the present study. Thus, by the results obtained in this study, the concentration of 30% P is recommended for the production of E. urograndis and E. saligna seedlings, while for E. dunnii it is necessary to use the standard level of P in nutrient solution for the adequate production of seedlings. However, it is necessary to carry out future studies with these genotypes from the P absorption kinetics, or through soil cultivation, to in order to confirm the efficiency responses to P observed in the hydroponic system experiment.